Analisis Pengaruh Corporate Social Respnsibility (CSR) Terhadap Masyarakat Kabupaten Rokan Hilir Provinsi Riau - Rahdiansyah; Shaleh, Ali Ismail (UIR Law Review, 2023)
Currently, the issue of Environmental Management is still a hot topic of discussion, especially regarding Environmental Management at the regional level. This research was conducted with the aim of understanding whether the local government has committed to environmental control. The method used in this research is descriptive research. By explaining what has been researched. The type of research in this writing includes the type of doctrinal/normative legal research. The data was collected by using a literature study technique, then processed in a qualitative way. There are several laws and regulations related to environmental control and management in Indonesia, namely Law no. 32 of 2009 concerning Environmental Protection and Management and several other laws. Given the condition of local governments that may still be far from the attention of the central government, local governments are now committed to realizing Environmental Management at their respective regional levels by using environmental-based budgets. However, there are still few local governments that use environmental-based budgets in managing environmental conditions in their areas.